Taxonomic Diversity of Soft-Bottom Ichthyofauna in the Lagoon of La Paz, B.C.S., México - Isaac, Acosta-Rodríguez; Emelio, Barjau-Gonzalez; Manuel, Lopez-Vivas Juan; Rachel, Castillo-Rosas Bruma; Karim, Romero-Piñera Abril; Angel, Armenta-Quintana Jose (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
The lagoon of La Paz has been affected by different anthropogenic activities, such as wastewater discharge and construction of marinas, which affect the local and transient ichthyofauna. Between august 2016 and June 2017, 2,763 organisms belonging to 72 species grouped in 51 genera were collected using an experimental trawl net. Temperature and dissolved oxygen presented a temporal variation, with August being the warmest month (28.17°C) and the lowest in oxygenation (12.44 mg*L), contrary to February (21.42°C) and June (21.9 mg*L). α-Fisher diversity was highest in Zacatecas (S=10.9); Las Palmas obtained the lowest (S=3.898). Alpha and average alpha diversities were highest in April (37, 11), beta diversity in August (3.4); lowest beta diversity was recorded in April (1.9), and lowest alpha during august (21). Taxonomic distinctness and average Taxonomic distinctness were highest in February (Δ*=85.95) and December (∆+=65.399); August recorded the lowest values (Δ*=50.55; ∆+=55.079). Variation in Taxonomic distincntess was highest in April (˄+=304.02) and lowest in august (˄+=304.02). Variability in such indices corresponds to the seasonal cycle of the Lagoon, with well-marked increases during the warm season, indicating stability in the conditions of the lagoon during the past years.